2006
DOI: 10.1191/0269216306pm1146oa
|View full text |Cite
|
Sign up to set email alerts
|

Who receives specialist palliative care in Western Australia - and who misses out

Abstract: Within a WA context, this study confirms established international evidence for problems of access to SPC by non-cancer patients and other disadvantaged groups. Importantly, this evidence is provided at a population level, thus documenting the extent of inequities in palliative care service provision. By pointing to the areas of most critical need, this study assists in health service policy and planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 67 publications
7
106
1
Order By: Relevance
“…We found that patients who had a PC referral were more often married than were patients without a PC referral, which has also been reported in other studies [17,20,25,26]. The reason for this observation is unknown, but it may be possible that a spouse acts as an advocate, lending a second voice to issues of symptom management at the end of life.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We found that patients who had a PC referral were more often married than were patients without a PC referral, which has also been reported in other studies [17,20,25,26]. The reason for this observation is unknown, but it may be possible that a spouse acts as an advocate, lending a second voice to issues of symptom management at the end of life.…”
Section: Discussionsupporting
confidence: 64%
“…We only identified a few studies that explored population databases [17,18] and surveyed families of cancer patients [19,20], although they did not assess PC referral patterns from an institutional perspective. Our institution is a National Cancer Institute designated comprehensive cancer center and includes an active PC program consisting of three mobile teams, an acute PC unit, and a supportive care clinic.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 This is much lower than statistics from other countries. The prevalence of hospice utilization has been reported as 65% in the United States, 9 19% (inpatient hospice) to 68% (hospice home care) in the United Kingdom, 10 65%-68% in Australia, 11,12 and 67% in Hong Kong. 13 In order to increase the utilization rate of hospice care in Taiwan, a new hospice consulting system with combined hospice care for cancer patients was recently propagated.…”
Section: Discussionmentioning
confidence: 99%
“…However, that study did not provide an estimate of the proportion of HCC patients who receive palliative care. In a retrospective cohort study of cancer patients using linked data from Western Australia, Rosenwax and McNamara (2006) found that, between 1 July 2000 and 31 December 2002, 68% of cancer patients received specialist palliative care in the last 12 months of life. This proportion is used in the present study.…”
Section: Economic Burden: Unit Costs Of Managing Patients With Chronimentioning
confidence: 99%